Challenges of the university in the face of climate change - Godenzi Alegre, Jorge Luis (2021)
Climate change as a challenge facing the University closely consistent with the message that works in the encyclical Laudato if recently published, in which the Pope Francisco wields great theological, scientific and moral arguments in order to develop strategies that has branded “urgent and compelling”. The Pontiff described with courage undisputed that this continuing damage causing him to come nature is like “a small sign of ethical, cultural and spiritual crisis of modernity”, the solution raises, require a high degree of sacrifice, which promptly called a “bold cultural revolution” worldwide. Indeed, and as proposed in this article and reaffirmed by the Pope in his encyclical, “Praise be” - that has been taken from the Canticle of St. Francis of Assisi - “There is a strong scientific consensus” that global warming Global is real and that his “main” cause us human; and continues to tell the pontiff that “immoral consumerism” is driving society to behavior that allows the continuous degradation of the environment. “The technology is based on highly polluting fossil fuels, especially coal, but even the oil and, to a lesser extent, expenditure needs to be replaced gradually and without delay? suggests this Church leader who has dared join Faith and science, God and the Earth and instead of rising to the heavens, shouting against sin, against faith and morals, has fallen to hell, the place of those in power than their greed for wanting to dominate the Earth, according to its capitalist calculations, prepare for new generations a planet “of debris, deserts and dirt.